2012
DOI: 10.1016/j.cjca.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Cardiac Remodelling in Rabbits Following Infarction

Abstract: Background Cardiac remodeling following myocardial infarction (MI) is a complex, dynamic process. There have been few longitudinal studies of these changes. Methods Two-dimensional transthoracic echocardiography was performed on 20 rabbits: before and 1, 2, 4, 8, and 12 weeks after MI (n=14) and twice for controls (n=6). Chronic left ventricular (LV) infarct size was histologically characterized and correlated with mechanical function. A linear mixed model was used to analyze longitudinal and infarct size re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results indicate that the cholesterol accumulated in the myocardium may be responsible for a reduction in myocardial strain. Similar to our study, Wang et al [ 23 ] reported a positive correlation between serum HDL levels and LVEF in human subjects with serum hypercholesterolemia even in the absence of angiographic evidence of CAD.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that the cholesterol accumulated in the myocardium may be responsible for a reduction in myocardial strain. Similar to our study, Wang et al [ 23 ] reported a positive correlation between serum HDL levels and LVEF in human subjects with serum hypercholesterolemia even in the absence of angiographic evidence of CAD.…”
Section: Discussionsupporting
confidence: 92%
“…Only animals developing a left ventricular dysfunction with ejection fraction inferior to 35% gained access to the second phase. Timing for second surgery was defined according to the reported findings of stabilization of cardiac remodeling process [ 23 ] and achievement of a histological plateau in the infarcted myocardium 4 weeks after MI induction [ 24 ]. To control for potential biases arising from the use of the biomaterial, results were compared also to a nonfunctionalized, pristine PLLA patch.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic ischaemia has been shown to induce adverse major structural and functional changes within the myocardium in both animal models and humans (1,2). During its evolution, cardiac remodelling during chronic ischaemia might involve several pathophysiological mechanisms (such as cardiomyocyte death, release of reactive oxygen species [ROS] and proteases, modifications of extracellular matrix, fibrosis, and inflammation), underlying postischaemic heart failure and potential arrhythmias (3,4).…”
Section: Introductionmentioning
confidence: 99%